2015
DOI: 10.3389/fcimb.2014.00194
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae biofilm formation and dispersion during colonization and disease

Abstract: Streptococcus pneumoniae (the pneumococcus) is a common colonizer of the human nasopharynx. Despite a low rate of invasive disease, the high prevalence of colonization results in millions of infections and over one million deaths per year, mostly in individuals under the age of 5 and the elderly. Colonizing pneumococci form well-organized biofilm communities in the nasopharyngeal environment, but the specific role of biofilms and their interaction with the host during colonization and disease is not yet clear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
163
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(181 citation statements)
references
References 165 publications
5
163
0
8
Order By: Relevance
“…Pneumococcal cells from these biofilms can be used to seed long-term, growing biofilms on live epithelial cells (52). Furthermore, bacteria in the biofilms growing on the fixed or live epithelial cells transition to virulent planktonic cells when the biofilms are exposed to stimuli produced during infections (52,65). We repeated FDAA long-pulsechase-new-labeling experiments with unencapsulated and encapsulated D39 strains growing in biofilms on fixed human epithelial cells ( Fig.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumococcal cells from these biofilms can be used to seed long-term, growing biofilms on live epithelial cells (52). Furthermore, bacteria in the biofilms growing on the fixed or live epithelial cells transition to virulent planktonic cells when the biofilms are exposed to stimuli produced during infections (52,65). We repeated FDAA long-pulsechase-new-labeling experiments with unencapsulated and encapsulated D39 strains growing in biofilms on fixed human epithelial cells ( Fig.…”
Section: Figmentioning
confidence: 99%
“…7). Hakansson and coworkers reported that encapsulated strains of S. pneumoniae, which do not form robust biofilms on abiotic surfaces, form physiologically relevant biofilms when in contact with fixed human respiratory tract epithelial cells (53,65). Pneumococcal cells from these biofilms can be used to seed long-term, growing biofilms on live epithelial cells (52).…”
Section: Figmentioning
confidence: 99%
“…Recent studies have shown that changes in the nasopharyngeal environment caused by concomitant virus infection, modifications in the microflora, inflammation or other host assaults trigger active release of pneumococci from biofilms. 26,27 These dispersed bacteria have distinct phenotypic properties and transcriptional profiles different from both biofilm and brothgrown, planktonic bacteria, resulting in a significantly increased virulence in vivo. 27 The higher risk of pneumococcal infections, including IPD, in DM1 patients compared with healthy subjects has been well known for many years and was recently confirmed by the observation that, despite the introduction of vaccine prophylaxis, it remained three times higher in the UK than in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 These dispersed bacteria have distinct phenotypic properties and transcriptional profiles different from both biofilm and brothgrown, planktonic bacteria, resulting in a significantly increased virulence in vivo. 27 The higher risk of pneumococcal infections, including IPD, in DM1 patients compared with healthy subjects has been well known for many years and was recently confirmed by the observation that, despite the introduction of vaccine prophylaxis, it remained three times higher in the UK than in the general population. [28][29][30] Finally, the incidence of staphylococcal infections in DM1 patients is not marginal and some of them can be particularly severe and difficult to treat.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest that this may explain long-term, asymptomatic nasopharyngeal colonization by S. pneumoniae in humans. Chao et al (2015) describe the increased propensity of S. pneumoniae in a biofilm to exchange genetic material. Mechanisms involved in dispersal during colonization and disease are also considered.…”
mentioning
confidence: 99%